Role of chaperone-mediated autophagy in the pathophysiology including pulmonary disorders - Yusuke Hosaka; Jun Araya; Yu Fujita; Kazuyoshi Kuwano (BMC, 2021)
Abstract Autophagy is a highly conserved mechanism of delivering cytoplasmic components for lysosomal degradation. Among the three major autophagic pathways, chaperone-mediated autophagy (CMA) is primarily characterized by its selective nature of protein degradation, which is mediated by heat shock cognate 71 kDa protein (HSC70: also known as HSPA8) recognition of the KFERQ peptide motif in target proteins. Lysosome-associated membrane protein type 2A (LAMP2A) is responsible for substrate binding and internalization to lysosomes, and thus, the lysosomal expression level of LAMP2A is a rate-limiting factor for CMA. Recent advances have uncovered not only physiological but also pathological role of CMA in multiple organs, including neurodegenerative disorders, kidney diseases, liver diseases, heart diseases, and cancers through the accumulation of unwanted proteins or increased degradation of target proteins with concomitant metabolic alterations resulting from CMA malfunction. With respect to pulmonary disorders, the involvement of CMA has been demonstrated in lung cancer and chronic obstructive pulmonary disease (COPD) pathogenesis through regulating apoptosis. Further understanding of CMA machinery may shed light on the molecular mechanisms of refractory disorders and lead to novel treatment modalities through CMA modulation.